MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: R

There are no items in this cart.
Continue Shopping
Menu
Nehal Gupta Grade: Upto college level
        Arg(z)-Arg(-z)=Arg(-1)=pi but Arg(-z)-Arg(z)=Arg(-1) is not equal to piexplain mathematically
6 years ago

Answers : (1)

kirti desai
16 Points
										

We have Arg(Z) - Arg(-z) = Arg(-1) = pi . this information is given.


now we have to prove that Arg(-Z) - Arg(Z) = Arg(-1) ≠ pi.


from given information we can write as,


Arg(-Z) = Arg(Z) - pi.


plug this value in Arg(-Z) - Arg(Z) , we get,


Arg(Z) - pi - Arg(Z) = -pi .thsi proves the result.

6 years ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies
  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: R 15,000
  • View Details

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details